Combining habitat loss and agricultural intensification improves our understanding of drivers of change in avian abundance in a North American cropland anthrome. Issue 3 (3rd January 2017) - Quinn, John E.; Awada, Tala; Trindade, Federico; Fulginiti, Lilyan; Perrin, Richard
Abstract: Identification of means to accommodate demand for food, fiber, and fuel while protecting biodiversity is essential. Given the scales of change associated with agriculture, effective analysis of the impact of biomass production on species abundance requires science and practice to address multiple measures of agricultural change. We analyzed the response of avian species abundance to multiple measures of agricultural change over a 40‐year period along the 41st parallel in the central United States, an area that is perhaps the most agriculturally expansive, intensive, and productive in the world. We prepared indexes of change for area farmed, chemicals used, and biomass produced. Competing singular and additive model combinations were evaluated using Akaike's information criterion model selection and used to estimate abundance of fifty‐five species of birds. The negative response of among grassland birds to both agricultural expansion and intensification suggests successful conservation in highly productive agroecoregions must consider elements of both land‐sparing and land‐sharing approaches. The response of nongrassland obligates to intensification and expansion was mixed, and conservation efforts may need to combine local and regional data to design successful management strategies. Inclusion of multiple processes of agricultural change provides greater insight for researchers, practitioners, and policymakers. These data provide evidence that a more comprehensive analysis of the relationship between North American biodiversity and agricultural production is necessary to improve conservation decision‐making and regional conservation prioritization. Abstract : Identification of means to accommodate demand for food, fiber, and fuel while protecting biodiversity is essential. We analyzed the response of species abundance to multiple measures of agricultural change over a 40‐year period along the 41st parallel in the central United States. These data provide evidence that a more comprehensive analysis of the relationship between North American biodiversity and agricultural production is necessary to improve conservation decision‐making and regional conservation prioritization.